Premature ovarian insufficiency and autoimmune diseases. (October 2019) - Domniz, Noam; Meirow, Dror
Abstract: Premature ovarian insufficiency (POI) is a clinical syndrome defined by loss of ovarian activity before the age of 40 years and has a potentially devastating effect upon women's health, both physically and psychologically. An underlying autoimmune disease has been identified in approximately 20% of patients with POI, the most common of which are disorders of the thyroid and adrenal glands. Nevertheless, in the majority of cases, the etiology is unknown. The damage mechanism to the ovary is usually caused by antibodies, and autoimmune POI is usually characterized by cellular infiltration of the theca cells of growing follicles by various inflammatory cells. Yet, other various factors and proteins of unknown clinical significance are present. The major diagnostic tool for otherwise idiopathic POI is the presence of autoantibodies against various ovarian components that strongly support the option of autoimmune etiology of POI. Treatment of the underlying cause of POI is the main strategy, although immunosuppressive therapy should be considered in a selected population of well-defined autoimmune POI and, as in idiopathic POI, in whom the resumption of ovarian activity is possible. Highlights: Premature ovarian insufficiency (POI) is one of the most severe conditions in reproductive medicine and poses a clinical challenge in both diagnosis and management. POI may be associated with several clinically apparent or sub-clinical autoimmune-mediated diseases from diverse genetic background and affect various organs. Ovarian autoimmunity is a well-established cause of ovarian insufficiency. Isolated POI, without an evidence of an autoimmune underlying disease, may be transient and part of the ovary may be functionally preserved. Management of POI patients should include a multi-disciplinary team.